Diseño de un sistema de control interno contable para una mueblería de Palmira – Valle (2022)
The present investigation was carried out with the objective of designing an internal accounting control system for a furniture store in Palmira - Valle del Cauca, for which a mixedtype study with a descriptive approach was carried out using the semi-structured interview. and the Internal Control Self-Assessment Questionnaire recognized as COSO III. The results allowed us to conclude that the furniture store under study has been carrying out a process of updating and administrative and financial organization, for which it has not currently formalized some aspects related to its strategic direction and organizational structure. However, from the management in charge of its owner, in the case of accounting and financial management, the functions related to the productive activity registered in the books are carried out and timely handling of supports and records is given. However, due to the lack of guidance, formally implemented operating manuals, standardization of procedures for agreements, accounting analysis and budget management, the design of an internal accounting control system became urgent. Said system consists of the control procedures to identify and classify the accounting and financial information, as well as to carry out records and adjustments and financial statements, taking into account both the productive activity and the current and real needs of the furniture store to optimize its management and make its productivity effective.